Soils and Fertilizers for Master Gardeners: Soil Physical Characteristics - Amy L. Shober; Alexander Joseph Reisinger; Mary G. Lusk; Sally Ann Scalera (EDIS)
Soils are a foundational component of the landscape, providing a medium for plant root growth and playing a crucial role in nutrient cycling and water movement across the landscape. This new 7-page article describes the physical properties of soils, including soil formation in Florida, the soil profile, and water dynamics within soils, and provides a thorough reference for Master Gardeners and other individuals searching for a basic understanding of soil dynamics to apply to residential landscapes. Written by Amy L. Shober, Alexander J. Reisinger, Mary G. Lusk, and Sally Ann Scalera and published by the UF/IFAS Department of Soil and Water Sciences. https://edis.ifas.ufl.edu/mg458